MARKETING STRATEGY FOR SMALL AND MEDIUM ENTERPRISE (SMES) OF COCONUT FURNITURE IN THE REGENCY OF TOMOHON MINAHASA, INDONESIA - Walukow, Ivoletti Merlina; Alelo, Maryke; Pangemanan, Shane Anneke (PEOPLE: International Journal of Social Sciences, 2018)
North Sulawesi, one of the provinces in northern part of Indonesia has an abundant coconut plantation which covers the area of more than 2.5 hundred thousand hectares. The coconut timber of this region has a harder and high density and is considered as the best of its kind throughout Indonesia. The coconut lumber has been widely used as building construction components and furniture. The latter has attracted the small and medium enterprise in Tomohon Minahasa to produce a high quality furniture. With the help of a foreign investment in machinery, this enterprise has been able to compete in the domestic market. However, recently it has faced a growing and intense competition from other alternatives that has significantly reduced the marketability and competitiveness of the coconut furniture. The research focuses on creating marketing strategy to this slow growth enterprise that will enable it to revive and recapture the lost marketsand develop new ones. The research methods employs a combination of observation, interview and questionnaire, documentation and analyzed usingIFE and EFE Matrices and Space Matrix . Thefinding shows that the enterprise is in Quadrant 4 which requires a competitive strategy. Product differentiation,backward and forward integration, networking and broadening marketing scale are among viable and feasible alternatives for this enterprise to not only survive but gain profitable end